Autoreceptor Control of Peptide/Neurotransmitter Corelease from PDF Neurons Determines Allocation of Circadian Activity in Drosophila - Charles Choi; Guan Cao; Anne K. Tanenhaus; Ellena v. McCarthy; Misun Jung; William Schleyer; Yuhua Shang; Michael Rosbash; Jerry C.P. Yin; Michael N. Nitabach (Cell Reports, 2012)
Drosophila melanogaster flies concentrate behavioral activity around dawn and dusk. This organization of daily activity is controlled by central circadian clock neurons, including the lateral-ventral pacemaker neurons (LNvs) that secrete the neuropeptide PDF (pigment dispersing factor). Previous studies have demonstrated the requirement for PDF signaling to PDF receptor (PDFR)-expressing dorsal clock neurons in organizing circadian activity. Although LNvs also express functional PDFR, the role of these autoreceptors has remained enigmatic. Here, we show that (1) PDFR activation in LNvs shifts the balance of circadian activity from evening to morning, similar to behavioral responses to summer-like environmental conditions, and (2) this shift is mediated by stimulation of the Gα,s-cAMP pathway and a consequent change in PDF/neurotransmitter corelease from the LNvs. These results suggest another mechanism for environmental control of the allocation of circadian activity and provide new general insight into the role of neuropeptide autoreceptors in behavioral control circuits.